A study of changing trends of maternal mortality at the tertiary care centre, MMC & RI Mysore, India - M, Ashraf Ali; MC, Babitha; HC, Lokeshchandra; Sharma, Kavya D.; Zehra, Maheen; Reddy, Madhuri S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal mortality is a reflection of the care given to women by the society. It is tragic that deaths occur during the natural process of child birth and most of them are preventable. Aims and objectives: To study the maternal mortality and the causes resulting in maternal death over 5 years in a tertiary care centre, Cheluvamba hospital, MMC & RI, Mysore. To find out avoidable factors and use information thus generated to reduce maternal mortality. Methods: A retrospective study of all maternal deaths from June 2008 to June 2013. All maternal deaths were reviewed and studied in detail including admission death interval and cause of death. Results: Maternal mortality ratio ranged between 262 to 109/100000 births. The causes of death were hypertensive disorders (30.4%), haemorrhage (24.8%), anaemia (14.8%), sepsis (6.8%) and others (23.2%). Maximum deaths (70.6%) occurred in women between 20-29 years of age, multigravida contributed to 54.96% of maternal mortality. 42 % were unbooked, 97% were referred cases. Conclusions: Overall maternal mortality was 215/100000 live births. Maternal deaths due to direct obstetric causes were 87% and indirect were 13 %. The causes of potentially preventable deaths include haemorrhage, anaemia, sepsis, disseminated intravascular coagulation and its complications. Hypertensive disorders were the leading cause of death, followed by haemorrhage. Anaemia was an important indirect cause of death. Most maternal deaths are preventable by optimum utilization of existing MCH facilities, identifying the bottlenecks in health delivery system, early identification of high risk pregnancies and their timely referral to tertiary care centre.